ChemInform Abstract: Triisopropyl Borate Mediated N‐Sulfinyl Imine Formation. Issue 31 (14th July 2016) - Visco, Michael D.; Reeves, Jonathan T.; Marsini, Maurice A.; Volchkov, Ivan; Busacca, Carl A.; Mattson, Anita E.; Senanayake, Chris H.
Abstract: Sulfinyl imines are prepared by condensation of aldehydes with sulfinamides in high yields.